Calcification score versus arterial stenosis grading: comparison of two CT-based methods for risk assessment of anastomotic leakage after esophagectomy and gastric pull-up - Chang DH; Brinkmann S; Smith L; Becker I; Schroeder W; Hoelscher AH; Haneder S; Maintz D; Spiro JE (Dove Medical Press, 2018)
De-Hua Chang,1,* Sebastian Brinkmann,2,* Lucy Smith,3 Ingrid Becker,4 Wolfgang Schroeder,2 Arnulf H Hoelscher,5 Stefan Haneder,1 David Maintz,1 Judith Eva Spiro6 1Department of Radiology, University Hospital of Cologne, Cologne, Germany; 2Department of General, Visceral and Cancer Surgery, University Hospital of Cologne, Cologne, Germany; 3Faculty of Medicine, Memorial University of Newfoundland, St John’s, Canada; 4Institute of Medical Statistics and Computational Biology, University of Cologne, Cologne, Germany; 5Agaplesion Markus Hospital, Frankfurt am Main, Germany; 6Department of Radiology, University Hospital, LMU Munich, Munich, Germany *These authors contributed equally to this work Purpose: Anastomotic leakage is a major surgical complication following esophagectomy and gastric pull-up. Specific risk factors such as celiac trunk (TC) stenosis and high calcification score of the aorta have been identified, but no data are available on their relative prognostic values. This retrospective study aimed to compare and evaluate calcification score versus stenosis quantification with regards to prognostic impact on anastomotic leakage.Patients and methods: Preoperative contrast-enhanced computed tomography scans of 164 consecutive patients with primary esophageal cancer were evaluated by two radiologists to apply a calcification score (0–3 scale) assessing the aorta, the celiac axis and the right and left postceliac arteries. Concurrently, the presence and degree of stenosis of TC and superior mesenteric artery were recorded for stenosis quantification.Results: Anastomotic leakage was noted in 14/164 patients and 12/14 showed stenosis of TC (n=11). The presence of TC stenosis was found to have a significant impact on anastomotic healing (p=0.004). The odds ratio for the prediction of anastomotic leakage by the degree of stenosis was 1.04 (95% CI, 1.02–1.07). Ten of 14 patients had aortic calcification scores of 1 or 2, but calcification scores of the aorta, the celiac axis and the right and left postceliac arteries did not correlate with the corresponding TC stenosis values and showed no influence on patient outcome as defined by the occurrence of anastomotic insufficiency (p=0.565, 0.855, 0.518 and 1.000, respectively). Inter-reader reliability of computed tomography analysis and absolute agreement on calcium scoring was mostly over 90%. No significant differences in preoperative comorbidities and patient characteristics were found between those with and without anastomotic leakage.Conclusion: Measurement of TC stenosis in preoperative contrast-enhanced computed tomography scans proved to be more reliable than calcification scores in predicting anastomotic leakage and should, therefore, be used in the risk assessment of patients undergoing esophagectomy and gastric pull-up. Keywords: TC stenosis, calcification score, anastomotic leakage, stenosis quantification, Ivor Lewis esophagectomy, graft perfusion